Maritime narcotics trafficking in the Western Indian Ocean: Threat to regional maritime security. (2nd January 2021) - Panneerselvam, Prakash
ABSTRACT: Maritime narcotics trafficking in the Indian Ocean has increasingly become a major security concern for India and other countries in the region, with the Afghanistan–Pakistan corridor being the primary conduit facilitating illegal drug trade via the sea-route in the Western Indian Ocean. However, there is a gap in understanding the extent and manner of the criminal syndicate involvement in the maritime narcotics drug trafficking in the region. This commentary looks at the emerging maritime-bound illicit drug trafficking in the region and also analyses the modus of operandi of the criminal syndicate in Pakistan to evade detection from the law-enforcement. It also examines the role of Combined Maritime Force (CMF) and regional navies in detecting and tracking the maritime narcotics trafficking in the Western Indian Ocean.